2021
DOI: 10.7759/cureus.13635
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pulmonary Hypertension With Inflammatory Markers and Volume Status in Hemodialysis Patients of End-Stage Renal Disease

Abstract: Background and objectives Pulmonary hypertension (PH) is an independent risk factor for increased mortality, especially in patients undergoing hemodialysis (HD), but the mechanism of its development is unknown. This study aimed at evaluating volume overload and inflammation as potential variables to cause its development in patients undergoing maintenance hemodialysis. Materials and methods This was an observational cross-sectional study conducted on patients undergoing hemodialysis at a tertiary hospital in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
4
1
1
Order By: Relevance
“…This study did not reveal any significant association with inflammation (CRP levels) and oxidative stress (MDA and thiol assay) in our hemodialysis patients. This is unlike the recent study by Sonkar et al (n=82) 7 wherein a higher level of inflammatory marker (alpha-1-acid glycoprotein) was seen in HD patients with PH. Another study by Smukowska-Gorynia et al 24 revealed higher levels of MDA in patients with PH but it included non-CKD and non-HD-dependent patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study did not reveal any significant association with inflammation (CRP levels) and oxidative stress (MDA and thiol assay) in our hemodialysis patients. This is unlike the recent study by Sonkar et al (n=82) 7 wherein a higher level of inflammatory marker (alpha-1-acid glycoprotein) was seen in HD patients with PH. Another study by Smukowska-Gorynia et al 24 revealed higher levels of MDA in patients with PH but it included non-CKD and non-HD-dependent patients.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the role of oxidative stress and inflammation in the development of PH is yet to be fully established. 7 …”
Section: Introductionmentioning
confidence: 99%
“…In their study, compared to normotensive patients, hypertensive patients were 3.2 times more likely to have PH (95% CI: 2.91-3.53; p < 0.001)[15]. These results are similar to studies done by Suresh et al[1], Tudoran et al[7], and Sonkar et al[14], which showed hypertension as a prevalent comorbidity in ESRD patients, which may have a role in the development of PH.The severity of PH was substantially correlated with the echocardiographic findings of RWMA, LVH, and LVEF. In our study, the prevalence of RWMA was higher in patients with mild PH (74.55%), moderate PH (80.6%), and severe PH (88.9%).…”
supporting
confidence: 79%
“…So sánh với các công trình nghiên cứu về tỷ lệ TAĐMP trên bệnh nhân LMĐK Thiếu máu, tăng cân giữa 2 lần lọc máu, rối loạn chức năng tâm thu và tâm trương của tim. Sonkar [12] Ấn Độ 43,48±14,65 82 25,6 Yếu tố viêm tăng, EF giảm CO: cung lượng tim, EF: phân suất tống máu.…”
Section: Mối Liên Quan Giữa Các Yếu Tố Nguy Cơ Với độ Nặng Của Tăng á...unclassified